2016
DOI: 10.1021/acs.joc.6b02038
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of d-Galactosamine and d-Allosamine Derivatives via a Microwave-Assisted Preparation of 1,6-Anhydroglucosamine

Abstract: We report a microwave-assisted intramolecular anomeric protection (iMAP) of glucosamine, which facilitates concise transformation of 1,6-anhydroglucosamine into 1,6-anhydrogalactosamine and 1,6-anhydroallosamine. The iMAP simultaneously obviates both the O1 and O6 protection, and the differentiation between O3 and O4 can be well-controlled by the N2 functionality because of the hydrogen bonding between N2 and O4. Epimerization of O4 afforded the galactosamine derivative and that of O3 yielded allosamine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Moreover, it is the main precursor in the synthesis of inhibitors for N-acetylneuraminidases from different sources [42]. The ring opening of 5 was not trivial since the substrate had a sterically hindered quaternary anomeric center, unlike the tertiary anomeric center C-1 of 1,6-anhydro sugars [29][30][31][32][33]43]. Furthermore, SnCl 4 and Sn(OTf) 2 might have formed a coordination bond with the carbonyl oxygen atom of the C-5 NHAc group and the O-6 position of the glucose glucopyranosyl ring.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it is the main precursor in the synthesis of inhibitors for N-acetylneuraminidases from different sources [42]. The ring opening of 5 was not trivial since the substrate had a sterically hindered quaternary anomeric center, unlike the tertiary anomeric center C-1 of 1,6-anhydro sugars [29][30][31][32][33]43]. Furthermore, SnCl 4 and Sn(OTf) 2 might have formed a coordination bond with the carbonyl oxygen atom of the C-5 NHAc group and the O-6 position of the glucose glucopyranosyl ring.…”
Section: Resultsmentioning
confidence: 99%
“…Our group has developed one-pot syntheses of several anhydro sugars via microwave (MW)-assisted intramolecular anomeric protection (iMAP) of silylated sugars as well as ring-opening protocols for their 1,6-anhydro bridges [29][30][31]. Accordingly, ᴅ-galactosamine and ᴅ-allosamine derivatives were synthesized Scheme 1: Concise synthesis of 2,7-anhydrosialic acid derivatives 2-6.…”
Section: Introductionmentioning
confidence: 99%
“…The preparation of tri-O-acetyl-D-glucal occurs in one pot without separation of the intermediate products. Triacetyl glucal was obtained in good yield by Dhurandhareetal [51]. In general, the anomeric protection can be followed the traditional protection and deprotection strategies, including peracetylation of azido hexose and its variety of oligosaccharide [52,53].…”
Section: Biocatalytic Potential Of Enzymes Involved the Modification Of Glucosamine In Chemotherapeuticalmentioning
confidence: 99%
“…Using the deacetylase enzyme which isolated from Cyclobacteriummarinum and these can all be used to convert the GlcNAc to glucosamine following two-steps strategies: (a) glycosidic bound cleavage of chitin to give intermediate GlcNAc by enzymatic processes, and (b) through selective enzyme which has ability for N-deacetylation GlcNAc to GlcN with high yield (Scheme 4) [54]. The GlcNAc is particularly obtained with acidic hydrolysis of chitin as in (Scheme 4), the GlcNAc converted to GlcN as intermediate [51,[55][56][57][58]. However, Petiard et al [59] reported that the extraction of GlcN from plants investigated with high temperature and low yield (Scheme 4).…”
Section: Biocatalytic Potential Of Enzymes Involved the Modification Of Glucosamine In Chemotherapeuticalmentioning
confidence: 99%
“…Another synthesis of a azidogalactosamine derivative involving inversion of the C4‐triflate was reported by Glibstrup and Pedersen using water and pyridine that involved migration of the participating benzoyl group at C3 . A variant utilizing the concept of intramolecular anomeric protection via a 1,6 anhydroglucosamine was also reported by Wang and co‐workers that involved inversion of the C4‐triflate using NaNO 2 …”
Section: Introductionmentioning
confidence: 99%